Whose Team Are You On? Evaluating Public Response to Native American Policy Priorities - Elise N. Blasingame (The Journal of Race, Ethnicity, and Politics, 2026)
Abstract Native American advocates and Tribal Nations have fought for decades against the use of Native imagery in sports mascots. In recent years, national sports franchises, colleges, and states have started responding to these demands by changing team names and iconography. As these policy changes have been framed as racial equity initiatives rather than matters of Native sovereignty, some professional teams continue to use Native imagery, and many states remain entrenched in debates over legislative mandates to remove such imagery from K-12 school sports. This project uses data from two survey experiments to examine how predominantly White fan bases respond to requests from tribal leaders, White allies, and partisan officials to support tribal policy priorities. Results indicate that the racial identity of the messenger significantly influences support for changing mascot practices, with Native messengers eliciting the strongest positive shifts in opinion.